KESANTUNAN KONVIVAL PADA MASYARAKAT BANJAR DI KELURAHAN SEKUMPUL, MARTAPURA - Rissari Yayuk (Balai Bahasa Nusa Tenggara Barat, 2017)
The purpose of this research is to study the socially-oriented culture with the social or Banjarconvention that is connected with the theory of language politeness based on pragmaticscience. The problem in this research is how to form the politeness of speech acts convulsivelanguage in Banjar society in Sekumpul Village, Martapura. This study used qualitativemethod. The author took three steps of work, namely the stage of data collection, dataprocessing, and presentation of data analysis. Techniques used in data retrieval arerecording and documentation techniques. Data analysis method is a method of matching.Data analysis techniques are the basic techniques of dividing as a distinguishing reactionand hearing rate. The result of this division will be obtained by analytical unit according towhat is meant by theory in literature review. Theories that become data analysis based onpragmatic science point of view. Presentation of datais using ordinary words.Researchlocation was in Sakumpul Village, Banjar District, South Kalimantan Province. The studywas conducted from January–June 2016. The result of the research showed that the form ofconvivial speech acts convulsive in Banjar society in Sekumpul Subdistrict, Martapura,consisted of conventional speaking speech acts convention offers, approves, apologizes,praises, approves, invites, Say hello, and congratulate.